Hubungan Harga Diri dan Optimisme Dengan Subjective well being Pada Aparatur Sipil Negara Dinas Pemberdayaan Perempuan dan Perlindungan Anak Di Kabupaten Tapanuli Tengah - Florensya Romauly; M. Rajab Lubis; Sjahril Effendy (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
This study aims to determine the relationship between self-esteem and subjective well being, the relationship between optimism and subjective well being, the relationship between self-esteem and optimism with subjective well being in the ASN of the Department of Women's Empowerment and Child Protection. This study uses a quantitative approach. The population in this study were 86 State Civil Servants using the total sampling technique. Based on data analysis, it is found that the hypothesis proposed in this study is accepted. This is evidenced by the calculation of multiple regression analysis, it can be seen with the correlation coefficient value rx1y = 0.895 with p = 0.000. This means that there is a significant positive relationship with self-esteem and subjective well being, the coefficient of rx2y = 0.950 with p = 0.000. This means that there is a significant positive relationship between optimism and subjective well being. Furthermore, based on the results of the analysis, the correlation coefficient value of rX1-X2-Y = 0.965 with p = 0.000 is obtained. This means that there is a relationship between self-esteem and optimism with subjective well being. The total contribution of self-esteem to optimism with subjective well being is 93.1%. These results show through the hypothetical mean of self-esteem (82.5 empirical mean 98.92). Optimism classified as high (hypothetical mean 65 empirical mean 80.50). Meanwhile, Subjective well being is classified as high (hypothetical mean 62.5 empirical mean 72.41.